Analysis of Problem-Solving Skills of Vocational Teacher Candidates in Terms of Several Variables - Anwar, Muhammad (Journal of Education Technology, 2021)
The learning strategy applied so far is still not optimal to develop students' thinking skills. Learning that includes problem solving skills to students as teacher candidates have not yet substantially implemented. This research aims to find learning methods that can improve students' thinking skills as teacher candidates, especially problem solving skills. This research was conducted using a descriptive type of general survey method. Using Slovin formula and 5% error, a sample of 340 students was proportionally selected from 2289 students as a population. Data collection using a problem solving skills questionnaire that rearranged based on the concept of the simplexity thinking process Basadur. However, this study shows that there are significant differences (p<0.05) from problem solving skills based on the level of satisfaction of teacher candidates to the learning methods implemented by lecturers. However, there were no significant differences in problem-solving skills based on course, gender, middle school background, and year of admission (p>0.05) after analyzed with one-way ANOVA. This study shows that satisfaction with learning is in line with the problem-solving skills of teacher candidates. Therefore, it is important for institutions that produce vocational teacher candidates to teach problem solving skills and maintain their level of satisfaction in the learning process.